The Scientific Approach Using Inquiry Learning Model in Improving Forehand Drive Performance of Table Tennis - Wahyudin Wahyudin; Saharullah Saharullah; Muhammad Aras Malik (Universitas Negeri Makassar, 2020)
This study aims to test an increase in the ability of a forehand drive in the game table tennis through the implementation of a scientific approach using inquiry learning model for one of Junior High Schools in South Sulawesi, Indonesia. This study applied a classroom action research conducted in two cycles. Each cycle consists of four steps, they are Planning, Implementation, Observation, and Reflection. Seventeen male students and eight females were involved as respondents in this study. Data collection techniques were conducted in the form of field observations and documentation. The data analysis technique used in this study was descriptive qualitative. This study found that the ability of the forehand drive of Junior High School students increased significantly from cycle I to cycle II. Learning outcomes in the first cycle in the complete category was 44%. In the second cycle, an increase of student learning outcomes in the complete category was 80%. Thus, learning table tennis through scientific application using inquiry learning models can improve the ability of students’ forehand drive.